Alpha2B-Adrenergic Receptor Overexpression in the Brain Potentiate Air Pollution-induced Behavior and Blood Pressure Changes. (25th January 2019) - Rao, Xiaoquan; Asico, Laureano D; Zanos, Panos; Mahabeleshwar, Ganapati H; Singh Gangwar, Roopesh; Xia, Chang; Duan, Lihua; Cisse, Yasmine-Marie; Rengasamy, Palanivel; Jose, Pedro A; Gould, Todd D; Nelson, Randy; et al.
Abstract: Fine ambient particulate matter (PM2.5 ) is able to induce sympathetic activation and inflammation in the brain. However, direct evidence demonstrating an essential role of sympathetic activation in PM2.5 -associated disease progression is lacking. We assess the contribution of α2B-adrenergic receptor (Adra2b) in air pollution-associated hypertension and behavioral changes in this study. Wild-type mice and Adra2b-transgenic mice overexpressing Adra2b in the brain (Adra2b Tg ) were exposed to concentrated PM2.5 or filtered air for 3 months via a versatile aerosol concentrator exposure system. Mice were fed with a high salt diet (4.0% NaCl) for 1 week at week 11 of exposure to induce blood pressure elevation. Intra-arterial blood pressure was monitored by radio-telemetry and behavior changes were assessed by open field, light-dark, and prepulse inhibition tests. PM2.5 exposure increased Adra2b in the brain of wild-type mice. Adra2b overexpression enhanced the anxiety-like behavior and high salt diet-induced blood pressure elevation in response to air pollution but not filtered air exposure. Adra2b overexpression induced upregulation of inflammatory genes such as TLR2, TLR4, and IL-6 in the brain exposed to PM2.5 . In addition, there were increased frequencies of activated effector T cells and increased expression of oxidative stress-related genes, such as SOD1, NQO1, Nrf2, and Gclm in Adra2b Tg mice compared with wild-type mice. Our results provide new evidence of distinct behavioral changes consistent with anxiety and blood pressure elevation in response to high salt intake and air pollution exposure, highlighting the importance of centrally expressed Adra2b in the vulnerability to air pollution exposure.